(untitled) (Pedagogy of Higher and Secondary Education, 2022)
This article considers the model of texis’ interpretation in the context of research activity of future lawyer. It determines models of realization future specialist interpret activity, underlines the role of hermeneutic approach based on cognitive method, reviews interrelation of ratio and emotion in the process of interpretation.